INTEGRATION OF REVEALED KNOWLEDGE INTO DESIGN THINKING: AN URBAN DESIGN STUDIO EXPERIMENT - Maharika, Ilya Fadjar (Journal of Islamic Architecture, 2018)
Integration of human knowledge principle has been widespread in the world of Islamic education, including in Indonesia. Partially seen as an attempt to build a school of thought of architecture education, the principle opens the discussion on the discursive level of design thinking. This paper reveals an explorative effort to translate the idea into a class experiment in an architectural design studio. This class experimental research uses a content analysis of students’ reflective writing who involve the design process that deliberately begins with the introduction of revealed knowledge (Arabic: wahy) in Architectural Design Studio 7 at the Department of Architecture, Universitas Islam Indonesia. In conclusion, it has formulated a dynamic and multi-dimensional construction of design thinking based on the integration of knowledge